Magnetic protein aggregates generated by supramolecular assembly of ferritin cages - a modular strategy for the immobilization of enzymes - Ölçücü, Gizem; Wollenhaupt, Bastian; Kohlheyer, Dietrich; Jaeger, Karl-Erich; Krauss, Ulrich (Frontiers in Bioengineering and Biotechnology, 2024)
Efficient and cost-effective immobilization methods are crucial for advancing the utilization of enzymes in industrial biocatalysis. To this end, in vivo immobilization methods relying on the completely biological production of immobilizates represent an interesting alternative to conventional carrier-based immobilization methods. In this contribution, we present a novel immobilization strategy utilizing in vivo produced, magnetic protein aggregates (MPAs). MPA production is facilitated by the expression of gene fusions consisting of genes encoding for the yellow fluorescent protein variant citrine and variants of the iron storage protein ferritin, including a magnetically enhanced ferritin mutant from Escherichia coli. Expression of the gene fusions allows supramolecular assembly of the fusion proteins in vivo, which is driven by citrine-dependent dimerization of ferritin cages. Upon cell lysis, the assemblies coalesce in solution to form MPAs. The fusion of the mutant E. coli ferritin to citrine yields fluorescent, insoluble protein aggregates that display magnetic properties, verified by their attraction to neodymium magnets. We further demonstrate that these novel, fully in vivo produced protein aggregates can be magnetically purified without the need for ex vivo iron-loading. Utilizing a bait/prey strategy, MPAs were functionalized by the post-translational attachment of an alcohol dehydrogenase to the MPA particles to enable proof-of-concept for enzyme immobilization, giving rise to catalytically-active magnetic protein aggregates (CatMPAs). The resulting (Cat)MPAs could easily be obtained from crude cell extracts via centrifugation, or purified using magnetic columns, and exhibited superior stability. The strategy presented here therefore represents a highly modular method to produce magnetic enzyme immobilizates which can be obtained with high purity.